2022
DOI: 10.1093/nutrit/nuab108
|View full text |Cite
|
Sign up to set email alerts
|

Repercussions of intermittent fasting on the intestinal microbiota community and body composition: a systematic review

Abstract: Context Several therapies have been tested for combating weight gain and obesity-related metabolic diseases, and among these therapies, intermittent fasting (IF) has gained a great deal of interest. Objective The aim of this study was to provide the reader with a current survey of IF protocols and an understanding of the outcomes found to date in terms of the profile of the intestinal microbiota (IM) in obese organisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…Owing to the small number of studied patients, the medium/high risk of bias of the available studies, and the current low level of evidence [54], further studies, assessing the mechanistic and functional aspects of microbiota-host relationships, are needed to better define the impact of TRE on human-gut microbiota.…”
Section: Tre and Microbiota Changesmentioning
confidence: 99%
“…Owing to the small number of studied patients, the medium/high risk of bias of the available studies, and the current low level of evidence [54], further studies, assessing the mechanistic and functional aspects of microbiota-host relationships, are needed to better define the impact of TRE on human-gut microbiota.…”
Section: Tre and Microbiota Changesmentioning
confidence: 99%
“…Intestinal microecology is a new aspect of the metabolic regulatory role of IF, and several studies have shown the potential of IF to alter flora composition. Pinto et al ( 100 ) recently published a systematic review on the role of IF in remodeling the gut microbiota in humans and rats/mice. In this study, the authors found that both alternate-day fasting and time-restricted fasting regimens altered the ratio of intestinal flora, mainly the Firmicutes/Bacteroidetes ratio and Lactobacillus spp abundance.…”
Section: Intermittent Fasting and Eye Diseasementioning
confidence: 99%
“…The gut microbiome, including the appendix that is now recognized as a non-vestigial well that maintains the microbiome [ 72 ], is recognized today for substantial influences on human health [ 30 , 31 , 32 , 73 , 74 , 75 , 76 ]. The microbiome impacts human health, both in the prevention of or acceleration of chronic diseases and in limiting or enhancing infectious diseases [ 16 , 30 , 31 , 32 , 73 , 74 , 75 , 76 ]. This includes the potential for acute infections in the intestine or in the appendix to radically alter organ-level health [ 73 , 74 , 75 , 76 ].…”
Section: Mechanisms Of Sars-cov-2 and Potential Opposing Effects Of F...mentioning
confidence: 99%
“…The microbiome impacts human health, both in the prevention of or acceleration of chronic diseases and in limiting or enhancing infectious diseases [ 16 , 30 , 31 , 32 , 73 , 74 , 75 , 76 ]. This includes the potential for acute infections in the intestine or in the appendix to radically alter organ-level health [ 73 , 74 , 75 , 76 ]. SARS-CoV-2 may be one of such infections, inducing gut microbiome dysbiosis that leads to enhanced proliferation of pathogenic microbial species, including anti-microbial resistant strains, and to the movement of harmful secondary pathogens into the bloodstream from the gut [ 30 , 73 ].…”
Section: Mechanisms Of Sars-cov-2 and Potential Opposing Effects Of F...mentioning
confidence: 99%